Perbedaan Metode Peer Teaching dengan Metode Jigsaw Terhadap Tingkat Pengetahuan Kesehatan Reproduksi - Solehati, Tetti; Anggraeni, Farina; Mardiah, Wiwi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2018)
Adolescents are particularly vulnerable to the problem of the triad of adolescent reproductive health that includes sexuality, HIV/AIDS and drugs. Lack of knowledge among adolescents is one of the causes of risky behavior on reproductive health. Health education through peer teaching method and jigsaw method can improve knowledge and prevent adolescent reproductive health problems. The purpose of this research is to analyze the differences between the effects of peer teaching method with jigsaw method toward the level knowledge of reproductive health students SMPN 1 Cilegon. The research design is quasi-experiment with non equivalent control group. The research sample consisted of 42 respondents to the peer teaching group and 42 respondents to the jigsaw group which is chosen by stratified random sampling. The results of the analysis of statistical tests using t-dependent test shows that there is significant influence after being given health education with p value 0.001 (p less than 0.05) and the results t-independent test obtained p value 0.021 (p less than 0.05), which shows the differences in effect between peer teaching method with jigsaw method toward the level knowledge of reproductive health students SMPN 1 Cilegon. The suggestion of this research is to use the jigsaw method as an alternative method in providing adolescent reproductive health education.